If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = 2(x + -5) Reorder the terms: 3(5 + x) = 2(x + -5) (5 * 3 + x * 3) = 2(x + -5) (15 + 3x) = 2(x + -5) Reorder the terms: 15 + 3x = 2(-5 + x) 15 + 3x = (-5 * 2 + x * 2) 15 + 3x = (-10 + 2x) Solving 15 + 3x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 3x + -2x = -10 + 2x + -2x Combine like terms: 3x + -2x = 1x 15 + 1x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 1x = -10 + 0 15 + 1x = -10 Add '-15' to each side of the equation. 15 + -15 + 1x = -10 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = -10 + -15 1x = -10 + -15 Combine like terms: -10 + -15 = -25 1x = -25 Divide each side by '1'. x = -25 Simplifying x = -25
| 12(x-1)=5(x-8) | | 4(x-8)=2(x+6) | | 9(x+6)=8(x+8) | | 2(3-x)+3(x-5)=0 | | 2(1-x)=3(2-x) | | 3(x-10)=2(x-15) | | (4-5i)(5-i)= | | 3(x-10)=3(x-15) | | 10(x+3)=5(x+4) | | 12(x+3)=7(x+8) | | 7x-6=4(5+5x) | | 2-4x=5(2x-8) | | mr=(1.97-(x+1)) | | 11(1-x)=44 | | 2(3+x)=8 | | 9c+c*2c-3=9 | | 6x^3-9x-x^5=0 | | -11(x-8)=44 | | 9(x-5)=2x-24 | | 2x+7y=-3 | | 4(x-6)=0 | | 7(5-x)=-14 | | 3(1-x)=6 | | 8(x+2)=-32 | | 2x-3=-3x+12 | | X=1-2.5y | | -5(x+7)=-40 | | 6x+15y=6 | | 21-4x=45 | | -10(x+1)=10 | | -2x^4+4x^3=0 | | 9(x-15)=9 |